The Amazon biome in messages: Public policy and communication frames on Telegram - Carneiro, Bia; Tucci, Giulia (2025)
This working paper investigates how the Amazon biome is represented and debated within Portuguese-language public Telegram channels, focusing on the intersection of environmental communication, digital disinformation, and public policy. Drawing on a dataset of over 39,000 messages from 605 Telegram channels between 2015 and 2025, the study applies digital methods—including topic modeling and network analysis—to uncover dominant narratives, influential actors, and discourse dynamics. Findings reveal that Telegram has become a central arena for Amazon-related discourse in Brazil, often surpassing traditional media in volume and intensity during key events such as forest fires and international summits. The platform’s affordances—such as large broadcast channels and low-friction forwarding—facilitate both genuine mobilization and the spread of disinformation. Narratives are shaped by polarization, securitization, and geopolitical framing, with topics like illegal mining and sovereignty frequently overshadowing ecological concerns. The study highlights the role of digital virality in amplifying strategic messaging and the risks posed by misinformation, which undermines climate action and public trust in science. It argues that protecting the Amazon requires not only ecological conservation but also safeguarding informational integrity. The authors call for integrated policy responses that address both environmental and digital governance challenges, emphasizing the need for climate literacy, platform accountability, and resilient public narratives.